2017
DOI: 10.1111/exd.13185
|View full text |Cite
|
Sign up to set email alerts
|

A review of genetic engineering biotechnologies for enhanced chronic wound healing

Abstract: Traditional methods for addressing chronic wounds focus on correcting dysfunction by controlling extracellular elements. This review highlights technologies that take a different approach -enhancing chronic wound healing by genetic modification to wound beds. Featured cutaneous transduction/transfection methods include viral modalities (ie adenoviruses, adeno-associated viruses, retroviruses and lentiviruses) and conventional non-viral modalities (ie naked DNA injections, microseeding, liposomal reagents, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 106 publications
(136 reference statements)
0
14
0
Order By: Relevance
“…Oral mucosal regeneration is an area of increasing research focus and includes the application of regenerative modalities such as 3D cell sheets consisting of oral mucosal cells (keratinocytes, fibroblasts, and endothelial cells) [2,3]. Genetic modification of such cell-based constructs may potentially further accelerate their healing capacity [4,5] and provide a novel strategy to promote wound healing in oral mucosa injury. Therefore, investigating the genetic mechanisms involved in the wound healing process of oral mucosa injury could be of significant translational value.…”
Section: Introductionmentioning
confidence: 99%
“…Oral mucosal regeneration is an area of increasing research focus and includes the application of regenerative modalities such as 3D cell sheets consisting of oral mucosal cells (keratinocytes, fibroblasts, and endothelial cells) [2,3]. Genetic modification of such cell-based constructs may potentially further accelerate their healing capacity [4,5] and provide a novel strategy to promote wound healing in oral mucosa injury. Therefore, investigating the genetic mechanisms involved in the wound healing process of oral mucosa injury could be of significant translational value.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment of the chronic wounds includes surgical debridement, biological dressing, pressure offloading, and topical growth factors. However, these methods provide very limited results in most cases (up to 50%) and new therapies are required to overcome the current challenges of chronic wound management (Greer et al, 2013; Dreifke et al, 2015; Rowan et al, 2015; Sessions et al, 2017). Recent studies have indicated that cell based therapies can provide a suitable alternative treatment method for multiple pathological conditions including, wound healing (Chen et al, 2012; Rodriguez-Menocal et al, 2015; Duscher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Scientists can induce permanent (gene insertions/deletion) or transient (transcriptional activation or inhibition) expression of growth factors/cytokines such as PDGF, VEGF, and hepatocyte growth factor 24 . There are many advantages of using CRISPR/Cas9 in chronic wound healing: relatively easier to build; capable to use gene library existed in the host genome instead of relying on inserting exogenous DNA; targeting multiple genes at the same time making it time‐saving and economically‐feasible 33 . While promising, further exploration is still needed to observe and establish its value in the field of wound healing.…”
Section: Gene Therapy and Wound Healingmentioning
confidence: 99%